Digesting the mechanobiology of the intestinal epithelium. (February 2022) - Pérez-González, Carlos; Ceada, Gerardo; Matejčić, Marija; Trepat, Xavier
Abstract : The dizzying life of the homeostatic intestinal epithelium is governed by a complex interplay between fate, form, force and function. This interplay is beginning to be elucidated thanks to advances in intravital and ex vivo imaging, organoid culture, and biomechanical measurements. Recent discoveries have untangled the intricate organization of the forces that fold the monolayer into crypts and villi, compartmentalize cell types, direct cell migration, and regulate cell identity, proliferation and death. These findings revealed that the dynamic equilibrium of the healthy intestinal epithelium relies on its ability to precisely coordinate tractions and tensions in space and time. In this review, we discuss recent findings in intestinal mechanobiology, and highlight some of the many fascinating questions that remain to be addressed in this emerging field.